2021
DOI: 10.5937/aaser2151049m
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rootstock on fruit physical properties of 'Pink Lady' apple

Abstract: During 2018 and 2019, we evaluated the main fruit physical properties [weight (FW), length (L), diameter (D), geometric mean diameter (Dg), length/diameter ratio (L/D ratio), sphericity (ph), surface area (S), fruit volume (V) and solid density (r)] of 'Pink Lady' apple grafted on dwarf M.9 T337, semi-dwarf M.26 and semi-vigour MM.106 rootstocks. Results showed that rootstocks significantly changed the properties evaluated with the exception of L/D ratio, ph and r. Among rootstocks, M.9 T33 7 produced the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…The exchange of P between sediment and water is complex phenomenon influenced by bacterial activity due to the abundance of PPB, out of total microbial mass of soils (Alongi, 1988). The bacterial ALP activity of sediments varied based on the physicochemical properties of soil, organic matter content, C/N ratio and total P content (Djordjevic et al, 2003). The increase in ALP activity in sediment samples of all treatment tanks with the PPB inoculum indicated that the inoculated bacterial isolates hydrolyze the organic phosphorus by producing extracellular phosphatases in the sediment which has remitted in the increase in the available P content in sediment and phosphorus in water.…”
Section: Alp Activity At Varying Salinitymentioning
confidence: 99%
“…The exchange of P between sediment and water is complex phenomenon influenced by bacterial activity due to the abundance of PPB, out of total microbial mass of soils (Alongi, 1988). The bacterial ALP activity of sediments varied based on the physicochemical properties of soil, organic matter content, C/N ratio and total P content (Djordjevic et al, 2003). The increase in ALP activity in sediment samples of all treatment tanks with the PPB inoculum indicated that the inoculated bacterial isolates hydrolyze the organic phosphorus by producing extracellular phosphatases in the sediment which has remitted in the increase in the available P content in sediment and phosphorus in water.…”
Section: Alp Activity At Varying Salinitymentioning
confidence: 99%